2008
DOI: 10.2341/07-28
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of One-step Polishing Systems on the Surface Roughness and Microhardness of Nanocomposites

Abstract: One-step polishing systems may be successfully used for polishing nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
3
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 26 publications
8
114
3
11
Order By: Relevance
“…Otherwise, the polishing agent will remove only the soft resin matrix and leave the filler particles protruding from the surface 34) . Studies have reported no appreciable differences in plaque accumulation among the surfaces polished by different methods and which resulted in Ra values within a range of 0.7-1.4 μm 6,35,36) . The highest mean Ra value for the composite materials tested in the present study was 0.20 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the polishing agent will remove only the soft resin matrix and leave the filler particles protruding from the surface 34) . Studies have reported no appreciable differences in plaque accumulation among the surfaces polished by different methods and which resulted in Ra values within a range of 0.7-1.4 μm 6,35,36) . The highest mean Ra value for the composite materials tested in the present study was 0.20 μm.…”
Section: Discussionmentioning
confidence: 99%
“…These advances contribute to the improved mechanical and physical properties of contemporary restorative composites. [1][2] The longevity of a composite restoration is directly related to the effectiveness of the adhesive system used, as the lack of bonding and inadequate marginal sealing may lead to restoration failure. 3 Current adhesive systems interact with the enamel/dentin substrate, using two different strategies: either removing the smear layer prior to bonding (etch & rinse technique) or maintaining the smear layer as the substrate and allowing its modification by a low pH primer-adhesive (self-etch technique).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, composite resin materials have also garnered a large following among patients with increased aesthetic expectations and demands. Improved formulations and simplified bonding procedures have endeared these materials to both patients and dentists alike [4][5][6] . Improvements in their mechanical and physical properties stem from reinforcing dental composites with filler particles, of which the filler concentration and particle size wield a significant influence 7) .…”
Section: Introductionmentioning
confidence: 99%